Effects of captopril and enalaprilat on intracellular Ca2+ content in isolated cardiomyocytes from rats - Wang Jun; Zhang Lu; Qi Jian-Hua; Zhang Pei-Jin; Wei Pei-Jing; Gu Pei-Kun; Jin Zheng-Jun (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of ACEI captopril (Cap) and enalaprilat (Ena) on intracellular Ca2+ concentration ([Ca2+]i) in cardiac myocytes isolated from SHR and WKY rats. METHODS: Using fluorescent probe Fura 2-AM combined with computer image processing technique to measure [Ca2+]i. RESULTS: Resting [Ca2+]i was higher in SHR cardiac myocytes (174 +/- 5 nmol.L-1) than that in WKY rat myocytes (148 +/- 15 nmol.L-1, P < 0.01). Cap and Ena decreased the resting [Ca2+]i in SHR myocytes (161 +/- 11 and 166 +/- 7 nmol.L-1, respectively, P < 0.05) but not in WKY rat myocytes (P > 0.05). Both drugs inhibited [Ca2+]i increment induced by KCI, NE, or Ang II in SHR and WKY rat myocytes except on KCI-induced [Ca2+]i increment in WKY rat myocytes (P > 0.05). CONCLUSION: Cap and Ena had direct effects on pathological voltage-operated calcium channel in cardiac myocytes.